ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN TENAGA ADMINISTRATIF DI FAKULTAS FARMASI UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Hidayati, Ana; Fudholi, Achmad; Sumarni, Sumarni (Universitas Ahmad Dahlan, 2014)
Student satisfaction measurement has been done with populatif observation and data collectedprospectively at the fourth level students of the Faculty of Pharmacy Ahmad Dahlan University. Thepurpose this study to describe and determine student satisfaction ratings gap that arises from servqual.The results obtained indicate generally that the service element in the Faculty of Pharmacy is namelyemployees has not given in accordance with the expectations of student performance is characterizedby a range of values of each gap there is nothing close to the ideal of zero (0). Gap values ofemployees in the education ministry on Tangible dimensions with a gap value -0,90, Reliability withthe gap value -0,90, Assurance gap value -0,90, Empathy with the gap value -1,10 andResponsiveness to the value gap -1,10 . While the reliability of the employee dimension into the first rank and dimensions of responsiveness on the faculty is considered the most excellent service tostudents.